How to Determine the Optimum Time to Harvest Hops - Shinsuke Agehara; Mariel Gallardo; Christopher DelCastillo; Weining Wang; Jack Rechcigl (EDIS, 2022)
This article explains how to determine the optimum time to harvest hops. It is part of a series that examines the challenges and opportunities of hop production in Florida based on research at the UF/IFAS Gulf Coast Research and Education Center (UF/IFAS GCREC). Written by Shinsuke Agehara, Mariel Gallardo, Christopher DelCastillo, Weining Wang, and Jack Rechcigl, and published by the UF/IFAS Horticultural Sciences Department; 4 pp. https://edis.ifas.ufl.edu/hs1436